Study of soft tissue sarcomas over a period of 3 years - Prabhakar, Jenna; Sushma, J.; Kartheek, B. V. S.; Lakshmi, A. Bhagya; Vaibhav, Chapara (International Journal of Research in Medical Sciences, 2017)
Background: Soft tissue malignancies constituted a heterogeneous group of rare solid tumors of mesenchymal cell origin with distinct clinical and pathological features. The aim of the study was to know the prevalence of soft tissue sarcoma, sex, age and site distribution, histopathology and various treatment options adopted with follow up. Methods: A total of 26 cases of soft tissue sarcoma were analyzed for a three-year period. Clinical presentation, age and sex distribution, histological type and treatment modalities adopted were recorded and analyzed. Results: Out of 26 cases 44% of cases were between 30-50 years and 44% of tumors were situated in lower extremity. The commonest histological type was liposarcomas and ﬁbrosarcoma. Lymph node metastasis was seen in 4% of cases. Distant metastasis was present in 3 cases, 2 with lung metastasis and l with lung and liver metastasis. Surgery was the main modality of the treatment. 12% of the cases presented with recurrent tumor, the duration between surgery and recurrence was 6 months. Only 38% turned for follow up, 2 patients succumbed to death because of multiple pulmonary secondaries and chest infections. Conclusion: In the present study, all the cases of soft tissue sarcoma presented in late stage of the disease due to illiteracy and lack of health education. Recurrence was seen in 12% of cases. The overall survival rates and quality of life of the patients can be improved by frequent health camps at primary health centers for early detection of the disease, providing adequate health education, diagnostic and management facilities.